AN ANALYSIS OF ILLOCUTIONARY ACTS IN GORDON RAMSAY COMMENTARY ON HELL’S KITCHEN SEASON 21 EPISODES 1-2 - Yuliani, Hanifah; Saehu, Andang; Budiarti, Dian (STKIP PGRI Tulungagung, 2024)
Communicating is a way for humans to convey information or messages that they want to share with others. Illocutionary acts often occur in everyday life related to speech acts between people. This research analyzes the illocutionary acts and how illocutionary acts are conveyed in the comments of Gordon Ramsay, who is a judge and head chef in the reality show Hell’s Kitchen Season 21 Episodes 1-2. The qualitative method with content analysis is used in this research. Data is taken from the available subtitle transcripts on each episode of this reality show. Searle’s theory is used to classify the types of illocutionary acts and then to identify the way of conveying illocutionary acts. This study found 94 data on the type of illocutionary act by direct and indirect speech acts. The findings showed the types of illocutionary acts were representative (36 data), expressive (29 data), directive (20 data), declarative (5 data), and commissive (4 data). Representative became the type of illocutionary act most used in this research. In addition, this illocutionary act is most often conveyed by direct speech acts, as much 73 data while indirect speech acts are 21 data. This type and method of conveying were most dominant because Gordon Ramsay’s comments contained statements and judgments about the participant’s dished and cooking skills based on his beliefs. Therefore, his comments directly state the meaning he wants to convey without hidden meanings.